Lots to Spot Flashcards My Food - Miles,Becky (Miles Kelly Publishing Ltd, 2019)
This captivating set of double-sided flashcards is designed to engage young children as they learn numbers, colors and simple words of familiar foods. The bold illustrations encourage learning through playing games and having fun.
Keywords: Flashcards Food